New Trace Bounds for the Product of Two Matrices and Their Applications in the Algebraic Riccati Equation - Jianzhou Liu; Juan Zhang (Journal of Inequalities and Applications, 2009)
By using singular value decomposition and majorization inequalities, we propose new inequalities for the trace of the product of two arbitrary real square matrices. These bounds improve and extend the recent results. Further, we give their application in the algebraic Riccati equation. Finally, numerical examples have illustrated that our results are effective and superior.